2001
DOI: 10.1093/humrep/16.9.2014
|View full text |Cite
|
Sign up to set email alerts
|

The role of genetic factors in age at natural menopause

Abstract: According to our findings, a woman with a family history of early menopause risks early menopause and consequently early reproductive failure herself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
127
0
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(137 citation statements)
references
References 16 publications
4
127
0
6
Order By: Relevance
“…Twin study has suggested that more than 60% of the AANM variation could be explained by the genetic factors [14][15][16]. However, very few genes have been reported to affect AANM [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twin study has suggested that more than 60% of the AANM variation could be explained by the genetic factors [14][15][16]. However, very few genes have been reported to affect AANM [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Family study showed that the menopausal ages of daughters were significantly correlated with mothers' [13]. Heritability estimates of AANM ranged from 0.63 to 0.87, suggesting a strong genetic control [14][15][16]. To date, the exact genes involved remain unknown, though some candidate genes underlying AANM have been proposed, such as ESR1 (estrogen receptor alpha), CYP1B1 (cytochrome P450, family 1, subfamily B, poly-peptide 1), Factor V Leiden, and FMR1 (fragile X mental retardation 1) [17][18][19][20].…”
Section: Introductionmentioning
confidence: 98%
“…We identified sister-and twin-pairs, of which both siblings participated in DOM, using probabilistic matching [17]. All data used for matching had been collected at the time of recruitment in DOM.…”
Section: Subjectsmentioning
confidence: 99%
“…In guppies, for example, the presence of predators results in a delay in the decline in reproductive potential compared with females in populations where predators are absent (Reznick et al, 2006). In humans, phenotypic variation in age at natural menopause also appears to be affected by factors such as smoking and diet (Nagata et al, 2000;Gold et al, 2001;de Bruin et al, 2001;Kok et al, 2005). The variation underlying rates of fertility loss are not only environmental.…”
Section: Introductionmentioning
confidence: 99%
“…The variation underlying rates of fertility loss are not only environmental. The age of onset of natural menopause in humans can be predicted by family history, with heritability estimates ranging from 0.30 to 0.85 (Kirk et al, 2001;de Bruin et al, 2001;Kok et al, 2005;Pettay et al, 2005;Broekmans et al, 2007). Linkage analysis of age at natural menopause has identified two significant quantitative trait loci influencing age at menopause (van Asselt et al, 2004).…”
Section: Introductionmentioning
confidence: 99%